Piórem niewieścim. Z problemów prozy kobiecej dwudziestolecia międzywojennego - Kraskowska, Ewa (Wydawnictwo Naukowe UAM, 1999)
The book explores some aspects of Polish prose written by women authors in the two decades between the World Wars.
Keywords: proza kobieca; dwudziestolecie międzywojenne; krytyka feministyczna